IMPLEMENTASI MANAJEMEN ORGANISASI BERBASIS ISLAM DI LEMBAGA PENDIDIKAN ISLAM: STUDI KASUS PADA LDK AL-IZZAH UINSU: PERSPEKTIF KEPEMIMPINAN DAN BUDAYA ORGANISASI - Wardani, Tika Kesuma; Marpaung, Syafri Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Campus Da’wah Institute (LDK) plays a strategic role as a non-formal educational institution that integrates students’ intellectual, emotional, and spiritual intelligence. This study aims to analyze the implementation of Islamic-based organizational management (POACE), the characteristics of prophetic leadership, and organizational culture at the Al-Izzah LDK at UIN North Sumatra. Using a qualitative descriptive method with a case study approach, data were collected through in-depth interviews, observations, and documentation of the core leadership. The results indicate that LDK Al-Izzah implements POACE functions integrated with Sharia, such as planning through the Dakwah Working Meeting (Mukerda), organization based on the “right man in the right place” principle, and transcendental oversight (muraqabah) through the “Tiket Syuro” regulation and a digital administrative system. Prophetic leadership is actualized through the qualities of Shiddiq, Amanah, Tabligh, and Fathonah (SATF), which are manifested in financial transparency, inclusive communication, and creative da’wah innovations. The organizational culture is strengthened by the value of Ukhuwah Islamiyah as a “lubricant” for internal conflicts, as well as the internalization of the slogan “Achieving Excellence, Spreading the Message of Islam” as a balancing force between academic and spiritual achievements. This study concludes that the integration of professional management, prophetic leadership, and a culture of ukhuwah are the main pillars of the effectiveness of campus da’wah organizations, although they still face challenges regarding the consistency of human resource engagement and schedule synchronization.